WiMax Network Design and Simulation for Middle Technical University Campus Using OPNET Modeler - Noman , Haeeder Munther; Hussein, Mohammed AbdulRidha; Abdulrazzaq, Ali Abdulwahhab (Iraqi Journal of Science, 2023)
This study aims to build a wireless computer network for a large company or university to enhance mobility and allow university users to stay connected at any time or place, which is achieved by applying the Universal Interoperability for Microwave Access (WiMax) technology. WiMax is based on the 802.16 sets of standards and has the most efficient and advanced hardware capabilities to meet the demands of teachers and students to browse the web or download files quickly. OPNET Modeler version 14.5 was used to determine the quality of service parameters of WiMax.